Construção da sensibilidade burguesa por meio do espaço em The Mysteries of Udolpho de Ann Radcliffe - Prado, Natália Cortez do (2016)
In the late eighteenth century, Ann Radcliffe established herself as one of the most famous novelists of her time, and she reached the peak of her career with her fourth novel entitled The Mysteries of Udolpho (1794). Although it is one of the most important gothic novels, this narrative has issues not much explored by critics yet. The Mysteries of Udolpho presents us with one of the strongest characteristics of Radcliffe s fiction, namely, the detailed construction of setting. In this sense, this work analyses and discusses the roles of setting, which is organized in the novel as natural or constructed setting. The analysis focuses on the relation between this thematic-formal aspect and the actions and personal relationships of the protagonist Emily with other characters. The discussion shows that the different types of setting are essential in the narrative once they have strong participation in the ideological construction of characters regarding the connection between sentimentalism and rationality. Therefore, the relation between setting and characters, in this particular novel, expresses important aspects of the complex development of the bourgeois sensibility in eighteenth-century England.